Estudio de prefactibilidad para la instalación de una planta procesadora de yogurt frutado de guanábana con chia - Paucar Roman, Diego Alexis Jesus (2021)
In this research work, you will develop the pre-feasibility study for the installation of a processing plant for fruity soursop yogurt with chia. Currently the average annual per capita consumption of yogurt in metropolitan Lima is 5.5 liters per person according to the National Institute of Statistics and Information (INEI, 2009). This dairy industry sector has strong growth potential according to: "Figures from the Euromonitor International consultancy, this market moved US $ 398 million last year, and in the next five years it may reach US $ 528.7 million." (Agrarian News Agency, 2017) In order to achieve a successful project, we will focus on developing a natural, rich product that stands out from our competitors. The fruit choice is soursop and the yogurt will be fruity so as to taste the texture of the fruit and the bittersweet taste. Likewise, soursop is a food that has a high nutritional value in vitamins and is consumed at any time of the day, whether at breakfast, mid-afternoon or at night, according to people's tastes and preferences. The product comes with chia, seeds are a source of omega 3 and has a high fiber content.And as a project we seek to generate a positive impact on the use of packaging and labels in order to contribute to the environment. In the first chapter, the uncertain and difficult path of products that are really natural without any type of sweeteners, flavorings and other types of additives is developed, to provide a healthy alternative. Additionally, the general and specific objectives will be established and the economic, technical and social justifications will be evidenced. In the same way, the working hypothesis is presented, the research scope and finally the conceptual framework is determined. In the second chapter, the market study is carried out in order to have a viable idea towards the developed project, the product is defined, the demand and supply analysis is carried out and the competitive and commercial strategy for the project is detailed. In the third chapter, the plant location is evaluated with the identification and analysis of Macro and Micro location factors using the Factor Ranking technique.